2017
DOI: 10.1542/peds.2017-1324
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Breastfeeding and Risk of SIDS: An Individual Participant Data Meta-analysis

Abstract: Breastfeeding duration of at least 2 months was associated with half the risk of SIDS. Breastfeeding does not need to be exclusive to confer this protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(74 citation statements)
references
References 23 publications
(16 reference statements)
2
63
0
9
Order By: Relevance
“…Current AAP guidelines unilaterally oppose bedsharing because of an association with SIDS . However, given that 1) breastfeeding is protective against SIDS; 2) bedsharing is consistently associated with longer durations of breastfeeding, in our data and others; and 3) many US women are bedsharing despite pediatrician advice not to, it seems that perhaps the time has come to revise this stance. Instead, honest, nonjudgmental, shared decision‐making conversations are necessary.…”
Section: Resultssupporting
confidence: 47%
“…Current AAP guidelines unilaterally oppose bedsharing because of an association with SIDS . However, given that 1) breastfeeding is protective against SIDS; 2) bedsharing is consistently associated with longer durations of breastfeeding, in our data and others; and 3) many US women are bedsharing despite pediatrician advice not to, it seems that perhaps the time has come to revise this stance. Instead, honest, nonjudgmental, shared decision‐making conversations are necessary.…”
Section: Resultssupporting
confidence: 47%
“…A recent meta‐analysis of individual data from eight case–control studies with a total of 2267 SIDS cases and 6837 control infants, showed that breastfeeding ≥2 months was protective. With greater protection seen with increased duration (2–4 months: aOR = 0.60, 95% CI = 0.44–0.82; 4–6 months: aOR = 0.40, 95% CI = 0.26–0.63; and >6 months: aOR = 0.36, 95% CI = 0.22–0.61) …”
Section: Evidence For Safe Sleeping Recommendationsmentioning
confidence: 99%
“…Formula feeding is associated with an increased risk of SIDS (Vennemann et al, ), likely due to decreased maternal and infant arousals with decreased synchronization of mother–infant sleep (Mosko, Richard, & McKenna, ). Breastfeeding beyond 2 months is associated with a lower risk of SIDS in a dose‐dependent fashion (Thompson et al, ). Videographic data show bedsharing positions in formula feeding dyads which are more likely to be hazardous (Ball, ), although other data show no increased risk of death from bedsharing and formula feeding if no other risks are present (Blair et al, ).…”
Section: Introductionmentioning
confidence: 99%